An integrative theoretical understanding of aggression: a brief exposition - Huesmann, L Rowell (Curr Opin Psychol, 2017)
Like other social behaviors, aggressive behavior is always a product of predisposing personal factors and precipitating situational factors. The predisposing factors exert their influence by creating encoded social cognitions including schemas about the world, scripts for social behavior, and normative beliefs about what is appropriate. These social cognitions interact with situational primes to determine behavior. These social cognitions are acquired primarily through observational learning; so youth who are repeatedly exposed to violence will acquire social cognitions promoting aggression that last into adulthood. Thus, violence can be viewed as a contagious disease which can be caught simply through its observation.